The Relationship Between Dreams and Subsequent Morning Mood Using Self-Reports and Text Analysis - Mark Blagrove (Affective Science, 2022)
While material from waking life is often represented in dreams, it is less clear whether and how dreams impact waking life. Here, we assessed whether dream mood and content from home diaries predict subsequent waking mood using both subjective self-reports and an objective automated word detection approach. Subjective ratings of dream and morning mood were highly correlated within participants for both negative and positive valence, suggesting that dream mood persists into waking. Text analyses revealed similar relationships between affect words in dreams and morning mood. Moreover, dreams referencing death or the body were related to worse morning mood, as was first-person singular pronoun usage (e.g., “I”). Dreams referencing leisure or ingestion, or including first-person plural pronouns (e.g., “we”), were related to better morning mood. Together, these results suggest that subjective experiences during sleep, while often overlooked, may be an important contributor to waking mood.